Salinity management in the delta of Senegal River Valley minimizing damage on rice growth and yield - CGIAR Research Program on Rice (2020)
Different agronomics options for salinity management were tested in 20 farmers fields in Senegal. Preliminary results showed rice yield increase by 0.6 t/ha (16%) compared to farmers? practices.